Two-dimensional mineral hydrogel-derived single atoms-anchored heterostructures for ultrastable hydrogen evolution - Lyu, Fucong; Zeng, Shanshan; Jia, Zhe; Ma, Fei-Xiang; Sun, Ligang; Cheng, Lizi; Pan, Jie; Bao, Yan; Mao, Zhengyi; Bu, Yu; Li, Yang Yang; Lu, Jian (Nature communications, 2022)
Hydrogen energy is critical for achieving carbon neutrality. Heterostructured materials with single metal-atom dispersion are desirable for hydrogen production. However, it remains a great challenge to achieve large-scale fabrication of single atom-anchored heterostructured catalysts with high stability, low cost, and convenience. Here, we report single iron (Fe) atom-dispersed heterostructured Mo-based nanosheets developed from a mineral hydrogel. These rationally designed nanosheets exhibit excellent hydrogen evolution reaction (HER) activity and reliability in alkaline condition, manifesting an overpotential of 38.5 mV at 10 mA cm −2 , and superior stability without performance deterioration over 600 h at current density up to 200 mA cm −2 , superior to most previously reported non-noble-metal electrocatalysts. The experimental and density functional theory results reveal that the O-coordinated single Fe atom-dispersed heterostructures greatly facilitated H 2 O adsorption and enabled effective adsorbed hydrogen (H*) adsorption/desorption. The green, scalable production of single-atom-dispersed heterostructured HER electrocatalysts reported here is of great significance in promoting their large-scale implementation. It remains a great challenge to achieve large-scale fabrication of single atom-anchored heterostructured catalysts with high stability, low cost, and convenience. Here, the authors report single iron atom-dispersed Mo-based nanosheets synthesized from a scalable two-dimensional mineral hydrogel approach for hydrogen evolution reaction in alkaline condition.